Review of marine alien isopods in Türkiye with two new records: of Paracerceis sculpta and Paranthura japonica - DAĞLI, ERTAN; BAKIR, KEREM; GÜNDEĞER, GIZEM; NERLOVIC, VEDRANA; DOĞAN, ALPER (Mediterranean Marine Science, 2024)
This study focuses on the alien isopod species recorded in the Turkish seas. To date, two alien species (Paradella dianae, Sphaeroma walkeri) have been reported in the country, accounting for almost 2.4% of the total number of isopod species occurring in the Turkish seas. The faunistic analysis of benthic samples collected from Dardanelles (Çanakkale) Straits and Izmir Bay revealed two new alien isopod species (Paranthura japonica and Paracerceis sculpta), on the Turkish coasts. Additionally, this is the first record of P. japonica in the Black Sea ecosystem. This study analyses and discusses the morphological, ecological and distributional characteristics of the species.